STANDARISASI AKAD JUAL BELI SYARIAH DAN HILANGNYA RUANG MUSYAWARAH DALAM PRAKTIK KONTRAK BISNIS ISLAM KONTEMPORER - Ahmad Alwi (Mukhtasab: Journal of Economics and Islamic Business, 2026)
The development of contemporary Islamic business is characterized by the increasing use of standardized sale contracts as a response to demands for efficiency, legal certainty, and the growing complexity of modern economic transactions. Contract standardization is considered an effective mechanism to streamline business processes and reduce legal risks, particularly within Islamic financial institutions and digital-based business platforms. However, the widespread application of standard contracts has raised a fundamental concern regarding the diminishing space for deliberation (musyawarah) between contracting parties, which potentially undermines ethical values and justice in Islamic commercial law. This study focuses on contemporary Islamic business contract practices by examining the position of standardized contracts and their implications for the principle of musyawarah as a core ethical and legal value in Islam. Employing a qualitative normative-empirical approach, the research analyzes Islamic jurisprudence on mu‘āmalah and Islamic business ethics, supported by document analysis of standardized contracts and selected business practices. The findings indicate that while standardized contracts enhance efficiency and legal certainty, their implementation often leads to bargaining power asymmetry and restricts meaningful participation in contract formation. This condition weakens the ethical dimension of contracts and risks distancing Islamic business practices from the principles of justice and deliberation. The study emphasizes the necessity of repositioning musyawarah within Islamic business contracts and advocates for the development of more participatory standardized contract models aligned with the normative objectives of Islamic law for both business actors and regulators.